’n Speelbaarheidsbenadering vir die vertaling van rolprente - Louis Calitz (Communicare)
This article argues that dubbing translation involves more than “mere” translation: it is the task of the dubbing translator to create dialogue that has to be spoken by dubbing actors and, for this reason, playability can be the only true test for the success of a dubbing translation. As no single definition exists for the term, insights from various disciplines, such as Visual Communication and Semiotics, are used to develop a model that would enable translators to create playable character dialogue for individual characters. The model is then tested by being used for the analysis of the German film Mephisto directed by Istvan Szabo.